Effectiveness and Eficiency of Educational Systems in a Context of Shifting Educational Paradigms - Želvys, Rimantas; Dukynaitė, Rita; Vaitekaitis, Jogaila (Pedagogika, 2018)
Neoliberal conceptions are pervading educational context worldwide. Lithuania is not an exception. Originally conceived as a sociocultural educational paradigm is being rapidly replaced by an economical paradigm. Constrained and short-sighted preoccupation with labour market needs is a sharp shift from humanistic and cultural vision of education as social good per se. Effectiveness and efficiency as an important endeavour of The New Public Management today permeates our education system. Data from international surveys show clear links between investment in education and student learning outcomes, yet, as EBPO PISA 2015 demonstrates, science classrooms in Lithuanian schools come short of laboratory equipment, leaving teachers with traditional chalk and talk methods, significantly lagging behind the international ones. We ask rhetorically “outputs without inputs”? Despite the criticism of narrow input-output mindset growing numbers of educational efficiency studies are observed. Moving away from economical concerns to focus on the educational process educational effectiveness research includes such variables as classroom microclimate, student motivation, socioeconomic and cultural status, which is proven to have tremendous influence on student learning outcomes and overall wellbeing. Effectiveness and efficiency research though seemingly complement each other but still rarely merge. Our most important educational documents – Lithuania’s progress strategy “Lithuania 2030”, National Education Strategy, Education Act, The Good School Concept are characterized by humanistic rhetoric stressing the importance of social and cultural aspects of education, but more than often indicators of success are oriented towards the implementation of the neoliberal economic education paradigm which leaves a lot to be desired.